Interactive structures visualizing structural behavior - Vassigh, Shahin (Wiley, 2005)
A learning tool that uses three-dimensional computer generated models, animations, audio narration, and interactive quizzes to communicate the fundamentals of structural behavior and analysis.--Disc container